PENERAPAN MODEL PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION (TAI) DAN TEAMS GAME TOURNAMENTS (TGT) PADA MATERI LINGKARAN DITINJAU DARI GAYA BELAJAR SISWA SMP DI KABUPATEN WONOGIRI - Murdoko, Yustinus; Mardiyana, Mardiyana; Usodo, Budi (Journal of Mathematics and Mathematics Education, 2017)
Abstract: The aim of the research was to determine the effect of learning models on mathematics achievement viewed from the student learning style. The learning models compared were TAI (Team Assisted Individualization), TGT (Teams Games tournament) and direct teaching learning. The type of the research was quasi-experimental research. The population was the students of junior high schoolÂ  in Wonogiri regency on academic year 2013/2014. The size of sample was 234 students consisted of 77 students in the first experimental group, 76 students on the second experimenta groupl, and 81 students on the tirth experimental group. The instruments used were mathematics achievement test, questioner, and the likert scale instrument. The data was analyzed using analisis of variance two way. Â Conclusions of the research were as follow. (1) the learning achievement of the students instructed with the TAI learning model is the same as that of the students instructed with the TGT learning model, and the learning achievements of the students instructed with the TAI learning model and that of the students instructed with the TGT learning model are better than that of the students instructed with the direct learning model; (1) the learning achievement of the students instructed with the TAI learning model is the same as that of the students instructed with the TGT learning model, and the learning achievements of the students instructed with the TAI learning model and that of the students instructed with the TGT learning model are better than that of the students instructed with the direct learning model; (2) the students with the visual, auditory, and kinesthetic styles have the same learning achievement in Mathematics; (3) in each learning model, the students with the visual, auditory, and kinesthetic learning styles have the same learning achievement in Mathematics; and (4) in each learning style, the learning achievement of the students instructed with the TAI learning model is the same as that of the students instructed with the TGT learning model, and the learning achievement of the students instructed with the TAI learning model and that of the students instructed with the TGT learning model are better than that of the students instructed with the direct learning model.Keywords: TAI, TGT, direct learning, learning style, achievement